Optimization method for precise control of proportional electromagnetic valve for automatic drive of agricultural machinery - GENG Biao; LI Huan; FANG Hui; ZHANG Shengrong; XU Wei (浙江大学学报. 农业与生命科学版, 2018)
To solve the problems of pulse width modulation (PWM) proportional solenoid valve control mode, such as large current ripple and low control precision, a method of dual PWM was adopted to control the proportional solenoid valve. Here, the dual PWM meant a second modulation was added in one PWM period. The results showed that this dual PWM can improve the control precision of the proportional solenoid valve, reduce the current ripple of proportional electromagnet, thus reducing the impulse of the proportional solenoid valve. As a result, it increased the life of solenoid valve, reduced the maintenance and replacement cost of product parts, and decreased the current fluctuation of the non-road mechanical products by nearly 1/3 in the shift, effectively slowing down the velocity jump caused by shifting and eliminating the sense of shift and frustration.